Analisis Dampak Live Music Dan Atmosfer Kafe Terhadap Kepuasan Pelanggan Kafe Legi Pait Surakarta - Muhammad Annang Fahmi Roziq; Agus Suyatno; Esti Dwi Rahmawati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to determine the effect of live music and café atmosphere on customer satisfaction at Legi Pait Food & Coffee Surakarta. This research uses quantitative research methods. The population in this research were customers of Legi Pait Food and Coffee Surakarta and the samples in this research was 67 respondents using simple random sampling. The variables usen in this research are Live Music, Café Atmosphere and Customer Satisfaction. The data used in this research is primary data. The data collection method used was a questionnaire in the form of a Google Form. The result of this research show that live music has a positive and significant effect on customer atisfaction, café atmosphere has a positive and significant effect on customer satisfaction and live music and café atmosphere simultaneously have a positive and significant effect on customer satisfaction.